The complete America's test kitchen TV show cookbook, 2001-2026 (America's Test Kitchen, 2025)
"Own the living archive of all of the recipes featured on public television's most popular cooking show, America's Test Kitchen. In this ATK cookbook you'll find almost 1400 recipes from all 26 seasons, every recipe from every show, an updated shopping guide for the latest top-rated equipment and ingredients, fewer chapters reorganized for easier navigation/use, a new Appetizers and Drinks chapter, anda new Vegetarian chapter. Join 2M weekly viewers as they cook alongside Bridget and Julia and the ATK experts to learn how to make dozens of new recipes. A comprehensive collection of recipes, product reviews, and tips, this is the perfect cookbook for beginners, more experienced home cooks, and all America's Test Kitchen fans"--